2017
DOI: 10.3928/01484834-20170918-08
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Placements in Geriatric Care Facilities: Students Gaining Experience With Challenging/Responsive Behaviors

Abstract: The students demonstrated good theoretical knowledge about responsive behaviors, but the lack of personal experience in managing such behaviors left the students feeling ill-prepared and distressed. Incorporating the opportunity to experience behaviors in a supported environment, such as in simulation, could reduce student distress and increase their sense of competency. [J Nurs Educ. 2017;56(10):623-627.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
1
1
1
Order By: Relevance
“…It is likely that the wide range is partly due to definitions of aggression, which vary between studies, and that the reality is somewhere in the middle. The noticeable difference was in the prevalence of physical violence which ranges from 8% to 42% in recent Anglo region studies (Clarke et al, 2012;O'Connell et al, 2017) compared with over half of participants in the current study. It may be that the placement circuit from this study is particularly dangerous, it could be that participation was more likely for students who had experienced physical aggression or again it could be related to definitions of physical aggression, which were purposefully broad in this study.…”
Section: Discussioncontrasting
confidence: 68%
“…It is likely that the wide range is partly due to definitions of aggression, which vary between studies, and that the reality is somewhere in the middle. The noticeable difference was in the prevalence of physical violence which ranges from 8% to 42% in recent Anglo region studies (Clarke et al, 2012;O'Connell et al, 2017) compared with over half of participants in the current study. It may be that the placement circuit from this study is particularly dangerous, it could be that participation was more likely for students who had experienced physical aggression or again it could be related to definitions of physical aggression, which were purposefully broad in this study.…”
Section: Discussioncontrasting
confidence: 68%
“…(14) However, educational plans vary in effectiveness (12) and, in some cases, workers may have theoretical knowledge but still feel unprepared to respond properly to a violent situation due to lack of experience. (15) In this sense studies have revealed the use of the simulation to reflect real situations inherent in the provision of care and its benefits to health training. (16)(17)(18) In general, the benefits include enhancing trust and knowledge, improving communication and criticality, promoting problem-solving skills, and managing complex situations.…”
Section: Introductionmentioning
confidence: 99%
“…Neste contexto, a literatura destaca também que apesar de bons conhecimentos teóricos os indivíduos ainda podem sentir-se despreparados para gerirem a violência no trabalho devido a falta de experiência (300) . Assim, uma revisão da literatura foi conduzida por nós e avaliou os resultados alcançados com o uso da simulação como ferramenta de intervenção em violência no trabalho com estudantes de enfermagem e trabalhadores de enfermagem.…”
Section: Parte Iv: Revisão Da Literaturaunclassified